Metformin environmental exposure: A systematic review - Ambrosio-Albuquerque, Eliane Papa; Cusioli, Luis Fernando; Bergamasco, Rosângela; Sinópolis Gigliolli, Adriana Aparecida; Lupepsa, Luara; Paupitz, Brennda Ribeiro; Barbieri, Pablo Américo; Borin-Carvalho, Luciana Andreia; de Brito Portela-Castro, Ana Luiza (Environmental toxicology and pharmacology, 2021)
This review discussed the occurrence, ecological impacts, and effects of metformin, a drug used for type 2 diabetes among other diseases. It is one of the most commonly found medicines in aquatic environments owing to its incomplete metabolism in the human body, and is eventually disposed in wastewater. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses were followed as a guide. After searching various databases, 48 eligible studies were selected for the review. Metformin reportedly occurs in different environmental matrices, as measurable concentrations of metformin are found in sewage (urban and hospital), influent/sludge/effluent from wastewater treatment plants, surface water (rivers, lakes, estuaries, oceans, and non-specific sources), tap/drinking water, and sediment (lake and recipient seawaters). Data on metformin detection in aquatic environments in 14 countries were studied, but a consensus on the risk patterns of pharmaceutical products was not determined. Many studies have been conducted on different test organisms, demonstrating that metformin can drive the expression of diverse genes, particularly those responsible for endocrine hormone pathways. Chronic exposure to metformin can be tested using models and other tools to understand this field, which remains largely unexplored. Our results contribute to the current ecotoxicology knowledge related to typically used drugs and provide a basis for further investigations.